Consumer Privacy Choice in Online Advertising: Who Opts Out and at What Cost to Industry? - Johnson, Garrett A.; Shriver, Scott K.; Du, Shaoyin (Marketing Science, 2020)
This paper studies consumers’ revealed privacy choice in online display advertising using real-world transaction data from an ad exchange.